(untitled) (MATEMATIKA, 2003)
This paper focuses on obtaining stability regions of numerical methods for ordinary differential equations (ODEs). In particular, the aim of this paper is to construct a stability region for method of Two Point Block Backward Differentiation Formulae (BDF). For the method to be of practical importance, the stability region must cover the whole of the negative half-plane. Keywords: Stability region; block; backward differentiation formulae.